Instrument and evaluation of students' involvement in learning Mathematics in 21-century skills at senior high schools of Riau province - Andrian, Dedek; Effendi, Leo Adhar (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Student engagement is the most crucial factor in learning activities because it is the main factor in improving student learning outcomes in class. This study aims to develop instruments and evaluate student involvement in learning mathematics to achieve maximum learning outcomes at school. The population in this study was all high school students in Riau Province. The sample is 150 high school students selected by multiple-stage random sampling based on high, medium, and low student achievement levels. Data analysis in this study was carried out four times: (1) data analysis based on the results of expert assessment of the instrument with the Aiken formula; (2) small-scale validity data analysis with first-order CFA; (3) large-scale data analysis with second-order CFA analysis; (4) descriptive analysis to see the categorization of student learning engagement in Riau Province whether in very good, good, not good and very not good. The analysis using the Aiken formula shows that 24 out of 27 items developed are valid. The first-order CFA analysis shows that the 24 items distributed are valid. The second-order analysis shows that the construct validity of the learning involvement variable is valid and reliable. The analysis of learning involvement results shows that students' involvement in learning mathematics is in the not-good category. The Riau provincial government needs to maximize student learning engagement which can be done by regulating students' effective study hours at school and home. Collaboration between parents and schools must be improved so parents can control student learning outside of school.